MASALAH PENGEMBANGAN POTENSI DESA DI DESA BULUH CINA KECAMATAN SIAK HULU - Asrida, Wan; Tinov, Tiyas; Gia, Paulus Edy (Nakhoda: Jurnal Ilmu Pemerintahan, 2011)
This research focuses on the the development of the Buluh Cina Village potency in the Siak HuluDistrict. The strategy for optimalization of the village potency is conducted by considering severalaspects such as housing and environment, natural disarter, education, health, socio-culture, economy,sport and amusement, transpotation, communication and information, land and its use and security. Thedata obtained in this reseach are collected using both direct questions to informant and from ducumentavailable in the village office and other sources. The data are then analyzed based on the research goals,presented by frequeny table and finally elaborated and explained. The results show that the Buluh Cinavillage contains substantial potency due to the availibility of fertile soils, river and its tributaries, swamparea and vast low land. The whole potency has not been used correctly, thus in ihe future could bedeveloped fully as village asset to increase its income. The results also indicate that fishery and touristmare the most potensial asset in Buluh Cina village.Keywords:development, potency